2011
DOI: 10.1159/000329155
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Working Memory in Alzheimer’s Disease Patients

Abstract: Background: Few studies have assessed whether emotional content affects processes supporting working memory in Alzheimer disease (AD) patients. Methods: We assessed 22 AD patients and 40 elderly controls (EC) with a delayed matching and non-matching to sample task (DMST/DNMST), and a spatial-delayed recognition span task (SRST; unique/varied) using emotional stimuli. Results: AD patients showed decreased performance on both tasks compared with EC. With regard to the valence of the stimuli, we did not observe s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 83 publications
1
15
0
1
Order By: Relevance
“…It is worth pointing out that other studies have also found no evidence that older adults are better in remembering positive stimuli (e.g. [60], [61]). …”
Section: Discussionmentioning
confidence: 76%
“…It is worth pointing out that other studies have also found no evidence that older adults are better in remembering positive stimuli (e.g. [60], [61]). …”
Section: Discussionmentioning
confidence: 76%
“…In fact, declines in general WM performance in DAT patients are well documented [12], while their ability to maintain and manipulate emotional information in WM is less certain [8][9][10][11]. The present study examined DAT patients' performance in a WM task, the operation span test, in which affective words were also presented.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, a series of previous studies with DAT patients has yielded mixed results. For example, Kensinger and colleagues [8] in a sentence generation task and with verbal descriptions [9] found no emotional enhancement effect, while Fleming et al, [10] in an immediate recall task for emotional words and Satler and Tomaz [11] who tested DAT patients' ability to recognize emotional information in a visuo-spatial WM task found emotional benefits. Consequently, generalizing WM emotional enhancement effects in DAT must be taken with caution and it may be that results depend on the type of WM task used.…”
Section: Introductionmentioning
confidence: 98%
“…In 2010, approximately 4.7 million individuals of 65 years old and more seasoned were living with Alzheimer's sickness in the US. Alzheimer's ailment association gives factual report an extent of the populace influenced a little more than a tenth of individuals in the more than 65 age bunch have the infection in the US in 2013 [10][11][12]. AD is the main source of dementia around the world, influencing more than half of the general number of deranged people, which has been assessed to associate with 24 million over all countries.…”
Section: Introductionmentioning
confidence: 99%